Modeling Extreme Meteorological Droughts From Paleo‐Climatic Reconstructions: A Metastatistical Framework - Maria Francesca Caruso; David Johnny Peres; Antonino Cancelliere; Marco Marani (Water Resources Research)
Abstract Droughts have pervasive societal impacts and remain difficult to characterize observationally, due to the limited number of droughts sampled in instrumental records. One approach to improving the statistical basis of drought occurrence probability estimation is to extend the observational record using proxy climatic archives, such as those based on tree‐ring information. Additionally, since droughts are rare and characterized by multiannual durations and inter‐arrival times, it is important to devise and apply statistical techniques that make full use of available information to improve our ability to quantify the rarest droughts. We extract data from a publicly available tree‐ring based Palmer Drought Severity Index (PDSI) data set, the Old World Drought Atlas, for two sites in Italy where long rainfall and temperature observational time series are leveraged for a meaningful comparison. Drought events are defined in terms of drought deficit volumes below a threshold PDSI value, and are studied through the Metastatistical Extreme Value Distribution (MEVD) to quantify the occurrence probability of extreme drought events. The estimation uncertainty associated with a variety of possible assumptions in MEVD analysis is studied, in specific comparison with the performance obtained using the traditional Generalized Extreme Value distribution, through a cross‐validation methodology. Results suggest that MEVD‐based formulations are more robust and flexible with respect to traditional ones. The combination of paleoclimatic data and methodologies capable of using most of the existing information provides more reliable estimates of drought recurrence times, which may be used to design more effective drought risk management plans.